Mempertahankan Eksistensi Radio Sebagai Media Dakwah (Studi Pada Radio Swara Dakwah Al-Amien Prenduan) - Ahmad Zulfikar Ali; Mohammad Fauzi (Dirosat : Journal of Islamic Studies, 2020)
The existence of an Islamic-based radio is felt to be very important considering that Islam must be widespread and conveying the truth is the responsibility of Muslims as a whole. In the midst of this situation, Radio Swara Dakwah Al-Amien Prenduan comes with an effective Islamic da'wah radio format which is always carried out by Islamic boarding schools. Al-Amien Prenduan for the creation of strong management-based institutionalization of da'wah. This research is intended to find out how the strategy used by Radio Swara Da'wah Al-Amien Prenduan (RASDA) FM 107.7 in maintaining its existence as a propaganda medium. This research is a qualitative research, with data collection techniques used are observation, interview and documentation methods. The analytical method used in this research is descriptive analysis to explain how the strategy is carried out to maintain its existence as a da'wah media. The results of this study indicate that in general the strategy used by Rasda radio in maintaining its existence is a communication strategy and radio broadcasting strategy. In particular, by implementing a communication strategy internally and externally. Internally, namely conducting evaluation meetings once a week and once a month. Externally, namely by expanding the network in the form of cooperation with other da'wah bureaus. While the factors that support Rasda FM as a da'wah media are the presence of sophisticated technological tools. The inhibiting factors are broadcasting and technical errors, such as lack of preparation, lack of concentration and damage to a device.